Ways to improve breast cancer patients' management and clinical outcome: The 2020 Assisi Think Tank Meeting. (September 2022) - Aristei, Cynthia; Bölükbaşı, Yasemin; Kaidar-Person, Orit; Pfeffer, Raphael; Arenas, Meritxell; Boersma, Liesbeth J.; Ciabattoni, Antonella; Coles, Charlotte E.; Franco, Pierfrancesco; Krengli, Marco; Leonardi, Maria Cristina; Marazzi, Fabio; et al.
Abstract: We report on the third Assisi Think Tank Meeting (ATTM) on breast cancer, a brainstorming project which involved European radiation and clinical oncologists who were dedicated to breast cancer research and treatment. Held on February 2020, the ATTM aimed at identifying key clinical questions in current clinical practice and "grey" areas requiring research to improve management and outcomes. Before the meeting, three key topics were selected: 1) managing patients with frailty due to either age and/or multi-morbidity; 2) stereotactic radiation therapy and systemic therapy in the management of oligometastatic disease; 3) contralateral breast tumour prevention in BCRA-mutated patients. Clinical practice in these areas was investigated by means of an online questionnaire. In the lapse period between the survey and the meeting, the working groups reviewed data, on-going studies and the clinical challenges which were then discussed in-depth and subjected to intense brainstorming during the meeting; research protocols were also proposed. Methodology, outcome of discussions, conclusions and study proposals are summarized in the present paper. In conclusion, this report presents an in-depth analysis of the state of the art, grey areas and controversies in breast cancer radiation therapy and discusses how to confront them in the absence of evidence-based data to guide clinical decision-making. Graphical Abstract: ga1 Highlights: Ultra-hypo-fractionated schedules appear safe and effective in the mid-term. Primary RT, ± ET, seems feasible for patients who are not candidates for surgery. SRT can be combined with systemic therapy in selected oligometastatic patients. Prophylactic RT might be an alternative to mastectomy in BRCA mutation carriers.